2017
DOI: 10.1177/1533034617740302
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive Body Setup Method for Radiotherapy by Using a Multimodal Image Fusion Technique

Abstract: Purpose:To minimize the mismatch error between patient surface and immobilization system for tumor location by a noninvasive patient setup method.Materials and Methods:The method, based on a point set registration, proposes a shift for patient positioning by integrating information of the computed tomography scans and that of optical surface landmarks. An evaluation of the method included 3 areas: (1) a validation on a phantom by estimating 100 known mismatch errors between patient surface and immobilization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As a result, surface deformation caused by respiration will lead to registration error that mainly consists of displacement in y and z directions as shown in Figure 4. Zhang’s previous study 10 showed an average final setup error of 1.30, 2.60, and 1.68 mm in x , y , and z directions, respectively. In comparison, our method exhibited a preferable accuracy in y and z directions, further indicating its effectiveness in reducing registration error caused by respiratory surface deformation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As a result, surface deformation caused by respiration will lead to registration error that mainly consists of displacement in y and z directions as shown in Figure 4. Zhang’s previous study 10 showed an average final setup error of 1.30, 2.60, and 1.68 mm in x , y , and z directions, respectively. In comparison, our method exhibited a preferable accuracy in y and z directions, further indicating its effectiveness in reducing registration error caused by respiratory surface deformation.…”
Section: Discussionmentioning
confidence: 87%
“…17 The MBSI will cause error between tumor center and LINAC isocenter after initial setup. 10 As a result, another transformation matrix M 1 should be applied to further adjust the position of vacuum cushion. M 1 is represented as…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the multi-resolution spline method is used to decompose images into a series of sub-band images with different resolutions, frequency features, and direction features, and then the weighted mean is calculated around the images overlapping boundary at each decomposed frequency domain. Finally, the composite images are stitched at all frequencies to form a complete image [14]. This method features higher computational complexity and higher fusion quality.…”
Section: Image Fusionmentioning
confidence: 99%